KARAKTER RABBANI SEBAGAI MEDIUM PEMBENTUKAN KECERDASAN SPIRITUAL DALAM PROSES PEMBELAJARAN (SEBUAH ANALISIS EMPIRIS PADA SDIT KOTA PALOPO) - Sitti Amrah (Islamic University of Indonesia, 2018)
Rabbani’s character emphasizes the functionalization of Godliness in the learning process through spiritual values, honesty, sincerity, compassion, tolerance, discipline, hard work, creative, independent, democratic, communicative and prioritizes emphasis on affective aspects (heart). Rabbani character has positive implications for fostering spiritual intelligence in the education process. The purpose of maximizing Rabbani character education in the context of learning is to actualize the potential of spirituality possessed by students, fostering sensitivity and religious responsibility of students through exemplary values, habituation, advice, warnings and punishments. Efforts to apply Rabbani character education in fostering spiritual intelligence can be initiated through the development of religious education curricula, familiarizing Islamic values, creating a cool and beautiful school environment, and applying disciplinary values in the learning process. The method used in the study is descriptive-analytical with interview methods to get maximum results. Keywords: Rabbani character, spiritual intelligence, religious culture.